À la naissance de deux graphèmes-symboles : LH et NH - Philippe Martel (Lengas)
Occitan language begins to be written as soon as the XIth century, for literary but also practical socio-economic uses. Therefore, the graphic system inherited from classical latin must be adapted, and new graphems designed, in order to permit a clear notation of new phonems, palatals for instance. It will be dealt in this paper with two examples : the invention during the XIIth century of -ch, -g (FACTU- >fach, fag, MEDIU- >mieg, and of lh nh (FILIA>filha, SENIOR > senher…), and the rapid spreading of those inventions throughout a good part of the occitan linguistic area.